Audit Fees During Initial Engagement in Malaysia - Abdul Wahab, Effiezal Aswadi; Zain, M. (Emerald Group Publishing Ltd., 2013)
Purpose – The purpose of this study is to investigate whether fees discounting exists in Malaysiaand whether such a practice impairs auditor independence.Design/methodology/approach – The paper employs a panel least regression of 3,003 firm-yearobservations of firms listed on Bursa Malaysia for the period between 1996 and 2006. The papercollects the audit fees, auditor’s identity and other firms’ characteristics data from Compustat Global,Stock Performance Guide Handbook and annual reports. The annual reports are obtained from theBursa Malaysia’s web site and Mergent Online database. The paper removes initial public offering(IPO) firms, firms involved with PriceWaterhouse and Coopers and Lybrand merger and firms forcedto switch auditor during the Arthur Andersen implosion in 2002.Findings – The analysis shows that price cutting occurs on initial audit engagements even when auditfees are publicly disclosed. Further tests suggest that the auditor recovers the “sunk cost” investedduring the initial engagement only during the fourth year of their audit engagement. Further, the paperfinds price recovery is not significantly different from normal audit fees charged for the continuingaudit engagement during the first three year period of engagement, as the audit firms will only recoverthe cost on the fourth year of engagement. Overall, this finding has an important implication forregulators, as it suggests that price recovery due to “lowballing” does not impair auditor independence.Research limitations/implications – Due to data unavailability, this study does not considerother unique factors that determine audit fees in Malaysia. Among them are political connections,institutional investors and ethnicity.Originality/value – This is the first study that examines audit pricing during an initial engagementin Malaysia.